European Union and World Order: An English School Approach - Stivachtis, Yannis (Estudos Internacionais: revista de relações internacionais da PUC Minas, 2015)
The concepts of ‘international system’, ‘international society’, and ‘world society’ are central to the English School’s approach to international relations. One of the major areas of inquiry within the English School has been the relationship between ‘international’ and ‘world society’. The paper discusses whether the creation of an ‘international society’ is a prerequisite for the establishment of a ‘world society’ or vice versa. It is argued that the European Union (EU) constitutes a 'thick' regional international society, which also includes significant elements of ‘world society’. EU's enlargement, neighbourhood, and development policies help to extend the elements of ‘world society’ beyond the boundaries of the EU thereby contributing to the creation of a world order based on European values and norms.